An initial examination of possible inferences concerning MSYR for Southern Hemisphere minke whales from recruitment trends estimated in catch-at-age analyses - Butterworth, D.S.; Puntt, A.E (J. Cetacean Res. Manage., 1999)
A slightly modified version of the BALEEN II population dynamics model, which makes allowance for time trends in carrying capacity K, is fitted to the recruitment time series provided by the base-case ADAPT VPA assessment of the catch-at-age and survey abundance data for minke whales in Area IV reported in Butterworth et al. (1999). The initial increasing trend of these recruitment estimates from 1944-1968 is well fitted by the model, yielding an estimate of MS¥Ryyu of some 13% (or MSYR,. of about 6%) which is reasonably robust to changes in a number of assumptions such as variation in the period over which K is assumed to increase, The post-1970 drop in recruitment indicated by the base-case ADAPT VPA assessment cannot be explained by the effects of catches and super-compensation alone, and requires the additional assumption of a recent decline in K. However, the need for this last assumption diminishes if allowance is made for likely negative bias in the absolute abundance estimates from the IWC surveys input to the ADAPT VPA assessments.